Aglycone production by Lactobacillus rhamnosus CRL981 during soymilk fermentation - Marazza, José Antonio (2009)
Lactobacillus rhamnosus CRL981 showed the highest levels of β-glucosidase and was selected to characterize this enzyme system, among 63 strains of different Lactobacillus species. The maximum activity was obtained at pH 6.4 and 42 °C. The enzyme showed weak resistance to thermal inactivation maintaining only 20% of the initial activity when it was exposed at 50 °C for 5 min. It also, showed stability when stored at 4 °C for 60 days. Afterwards, L. rhamnosus was evaluated for hydrolysis of isoflavones to aglycones, cell population, residual sugars and organic acid produced during fermentation on soymilk (37 °C for 24 h). Higher viable counts were obtained after 12 h of fermentation (8.85 log CFU ml-1) followed by a drop of pH and an increase of acidity during fermentation due the production of organic acids. L. rhamnosus CRL981 was able to proliferate in soymilk and produce a high β-glucosidase activity achieving a complete hydrolysis of glucoside isoflavones after 12 h of fermentation. The present study indicates that L. rhamnosus CRL981 could be used in the development of different aglycone-rich functional soy beverages.